Anti‐biofilm and antibacterial activities of zinc oxide nanoparticles against the oral opportunistic pathogens Rothia dentocariosa and Rothia mucilaginosa. (14th October 2014) - Khan, Shams T.; Ahamed, Maqusood; Musarrat, Javed; Al‐Khedhairy, Abdulaziz A.
<x xml:space="preserve">Abstract</x> Species of the genus Rothia that inhabit the oral cavity have recently been implicated in a number of diseases. To minimize their role in oral infections, it is imperative to reduce and/or control the growth and biofilm formation activity of Rothia spp. In this study, two bacterial isolates, Ora‐7 and Ora‐16, were obtained from the oral cavity of a healthy male subject and identified as Rothia dentocariosa and Rothia mucilaginosa, respectively, using a polyphasic taxonomic approach. Antimicrobial and anti‐biofilm formation activities of zinc oxide nanoparticles (ZnO‐NPs), of average size 35 nm, were assessed in in vitro assays using Crystal Violet and live and dead staining techniques. The ZnO‐NPs exhibited an IC50 value of 53 and 76 μg ml−1 against R. dentocariosa and R. mucilaginosa, respectively. Biofilm‐formation assays, performed on the surfaces of polystyrene plates, artificial teeth, and dental prostheses, revealed the efficacy of ZnO‐NPs as a potential antibacterial agent for controlling the growth of Rothia isolates in both planktonic form and biofilm.